2013
DOI: 10.1590/s0001-37652013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Copper Stress on Photosynthesis of Black Mangle (Avicennia germinans)

Abstract: The effects of copper toxicity on the photosynthetic activities of Avicennia germinans was investigated using two CuSO 4 concentrations (0.062 and 0.33 M) added in Hoagland's solution in an aerated hydroponic system. Photosynthesis and chlorophyll fl uorescence were measured after 30 h of copper stress. Results obtained in this study show that increasing levels of Cu +2 of 0.062 and 0.33 M Cu +2 resulted in a general reduction of the stomatal conductance (28 and 18%, respectively) and 100% of inhibition of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 14 publications
5
19
0
Order By: Relevance
“…1a). Similar to these results, photosynthesis was decreased by copper in the sensitive Silene paradoxa L. populations, black mangle, and in red algae Antithamnion plumula (Gonzalez-Mendoza et al, 2013;Bazihizina et al, 2014;Zou et al, 2015). In addition, the excess copper decreased chloroplast pigment (including chlorophyll and carotenoids) concentration in the dinoflagellate Cochlodinium polykrikoides , as well as in the diatom Phaeodactylum tricornutum .…”
Section: Effects Of Excess Copper On Chloroplasts and Mitochondriasupporting
confidence: 76%
See 1 more Smart Citation
“…1a). Similar to these results, photosynthesis was decreased by copper in the sensitive Silene paradoxa L. populations, black mangle, and in red algae Antithamnion plumula (Gonzalez-Mendoza et al, 2013;Bazihizina et al, 2014;Zou et al, 2015). In addition, the excess copper decreased chloroplast pigment (including chlorophyll and carotenoids) concentration in the dinoflagellate Cochlodinium polykrikoides , as well as in the diatom Phaeodactylum tricornutum .…”
Section: Effects Of Excess Copper On Chloroplasts and Mitochondriasupporting
confidence: 76%
“…Photosynthesis in photosynthetic organisms is sensitive to environmental variation (Jamers et al, 2006;Gonzalez-Mendoza et al, 2013;Bazihizina et al, 2014;Zou et al, 2015). As expected, excess Cu 2+ caused a decrease in the photosynthetic efficiency of Prorocentrum minimum (Fig.…”
Section: Effects Of Excess Copper On Chloroplasts and Mitochondriasupporting
confidence: 71%
“…It may indicate that Fv/Fo and Fo/Fv parameters are the most sensitive components in the photosynthetic electron transport chain in the presence of high copper concentration. In agreement to these results, it has been previously confirmed that the Fv/Fo and Fo/Fv parameter are the most sensitive component of PSII under undesirable conditions (González-Mendoza et al, 2013). Similar results were observed by and Singh et al (2013) who reported that higher concentrations of heavy metals induced one rapid inactivation of PSII in Luffa acutangula under hydroponics conditions.…”
Section: Time Of Exposure (H)supporting
confidence: 86%
“…The chlorophyll fluorescence was measured using a Plant Efficiency Analyser (PEA, Hansatech Instruments Ltd., King's Lynn Norfolk PE32 1JL, UK) on completely expanded leaves. The leaves were subjected to a 5 min period of adaptation to darkness under to induce the complete oxidation of the reaction centers using light exclusion clips (González-Mendoza et al, 2013).…”
Section: Bioaccumulation and Changes In The Photosynthetic Apparatus mentioning
confidence: 99%
“…Excess Cu in plant tissues resulted in detrimental effects for the photosynthetic machinery, as indicated by the chlorophyll fluorescence parameters (González-Mendoza et al, 2013). Increases in minimal fluorescence (Fo) result from the destruction of photosystem II (PSII) reaction centers or decreased transfer of excitation energy to the reaction center caused by excess Cu in the plant tissues (Baker and Rosenqvst, 2004).…”
Section: Discussionmentioning
confidence: 99%